IDEOLOGI GENDER KEBAHASAAN PADA NOVEL KARYA SASTRA PENGARANG PEREMPUAN - Heny Roulina Sitepu; T Silvana Sinar; Irawaty Kahar (Balai Bahasa Sumatera Utara, 2019)
The novel by female authors often tell about the position of women who appear as symbols of subtlety, and place them in a lower position than men. The purpose of this study is to analyze how the form of linguistic gender ideology in literary novels by female authors and what context triggers gender ideology in novels by literary authors. In this study, researchers focused on this research on the Mills Kritsis Discourse Analysis. This research is a type of qualitative research. The data in this study is sentences that contain linguistic by female authors. Data collection techniques in this study use document recording techniques. Based on the results of data analysis it is known that the form of linguistic gender ideology in literary novels of female authors is dominated by the form of subordination that is 20 data or about (60.53%), while 18 (14.37%) other data leads to stereotypes for readers of literary novels, especially literary works of female authors, to foster interest in preserving literary novels, especially literary novels, especially authors